Kewajiban Perusahaan Membayar Pesangon Sebagai Bentuk Memenuhi Hak Karyawan Jika Terjadi Pemutusan Hubungan Kerja: Studi Kasus Pemutusan Hubungan Kerja di PT Duta Tambang Rekayasa - Desi Wilda Rizki Amelia; Nur Arifudin; Ziana Walidah; Alifia Nur Iddhiyan; Surfadila Surfadila (Lembaga Pengembangan Kinerja Dosen, 2024)
Termination of employment is the end of an employment relationship due to certain things that cause the end of the rights and obligations between workers/laborers and employers. What are the company's obligations, one of which is paying severance pay as compensation for termination of employment (PHK). Termination of employment is regulated in the Job Creation Law no. 11 of 2020 due to several reasons that give rise to termination of employment based on law, which aims to obtain the rights obtained for workers regarding the severance pay they receive.